Decision economics : some guidelines for managers - Oxenfeldt, Alred R (Canterbury Financial World Pub., 2001)
These concise business books are of vital interest to managers and professionals who must measure time carefully and maintain a broad acquaintance with basic current knowledge and management practice.
rpm 16/08/16
Loans
Keywords: Decision making; Decision economics